Vocational Counseling or Vocational Guidance? - Patterson, C. H.; Memphis State Univ., TN. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
All professional persons engage in a number of activities, but they perform one major function, and their profession is designated by a word which indicates this major function. Counselors are usually called guidance counselors, partly because of their many other activities besides counseling, and partly because many counselors do little or no counseling, but rather direct and control. If another term is needed, perhaps psychological counselor would be more valid. In vocational counseling, the counselor does not guide students into particular occupations or fields. The focus of counseling - vocational counseling - is upon the interests and abilities of the client and their implications for vocational development and choice. The client's exploration and thinking should be free of constraints or restrictions on the opportunities and demands in society. Only in the final choice should these external "reality" factors enter in. Society and industry should not suffer from such an approach, since each individual would be enabled to do that for which he is best suited and in which he is most interested. The function of a counselor is to help the student find a vocation which utilizes his abilities and satisfies his interests and needs, not to guide him along paths determined by someone else. (KJ)
ERIC Note: Paper presented at the Vocational Guidance Institute, Memphis State University, Memphis, Tennessee, June 17, 1969.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Counselor Evaluation; Guidance Programs; Career Counseling; Counseling Theories; Counselor Role; Counselors; School Counseling